# Step-by-step Solution

## Factor the expression $x^2-2x+1$

Go!
Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

### Videos

$\left(x-1\right)^{2}$

## Step-by-step Solution

Problem to solve:

$factor\left(x^2-2x+1\right)$

Choose the solving method

1

The trinomial $x^2-2x+1$ is a perfect square trinomial, because it's discriminant is equal to zero

$\Delta=b^2-4ac=-2^2-4\left(1\right)\left(1\right) = 0$

Learn how to solve factorization problems step by step online.

$\Delta=b^2-4ac=-2^2-4\left(1\right)\left(1\right) = 0$

Learn how to solve factorization problems step by step online. Factor the expression x^2-2x+1. The trinomial x^2-2x+1 is a perfect square trinomial, because it's discriminant is equal to zero. Using the perfect square trinomial formula. Factoring the perfect square trinomial.

$\left(x-1\right)^{2}$
SnapXam A2

### beta Got another answer? Verify it!

Go!
1
2
3
4
5
6
7
8
9
0
a
b
c
d
f
g
m
n
u
v
w
x
y
z
.
(◻)
+
-
×
◻/◻
/
÷
2

e
π
ln
log
log
lim
d/dx
Dx
|◻|
θ
=
>
<
>=
<=
sin
cos
tan
cot
sec
csc

asin
acos
atan
acot
asec
acsc

sinh
cosh
tanh
coth
sech
csch

asinh
acosh
atanh
acoth
asech
acsch

$factor\left(x^2-2x+1\right)$